EMG frequency spectral characteristics of inspiratory accessory muscles during the shoulder lifting motion in throwing athletes - Hartz, Charlini Simoni; Pires, Paulo Fernandes; Moreno, Marlene Aparecida; Bigaton, Delaine Rodrigues (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Background: Dysfunctions related to the shoulder joint are very common in throwing athletes, due to the overhead generated in repetitive movements with your arms above your head. In addition, in handball, the movements are of high intensity, which generates a large metabolic demand and high ventilatory demands. Studies show that highest work of the respiratory muscles, coupled with high mechanical requirement in the upper limbs, generates a dual requirement under the inspiratory muscles in these athletes, leading to limitations related to muscle fatigue. Objective: The objective of this study was to evaluate the EMG frequency spectral characteristics (fatigue index) to accessory muscles of inspiration, through the induction of shoulder elevation movement in handball athletes. Method/Design: The sample consisted of 25 male athletes with an average age of 20 years. Fatigue index was measured by surface electromyography (mean and median frequency - Hz), in which the volunteers performed isometric movement of elevation of the shoulders, and after collection, the data were processed off-line on Matlab R2014a software. For statistical analysis used the Shapiro-Wilk test to test the normality of the data, followed by the comparison of data through the Student t test for independent samples. Significant difference was considered for p value <0.05. Results: The results showed a significant difference between the mean and median frequency values for the sternocleidomastoid muscle right compared to the left sternocleidomastoid muscle. Conclusions: We conclude that during isometric movement of shoulder elevation, there was asymmetry in the frequency spectral characteristics of only one accessory muscles of inspiration, presenting asymmetry, and greater fatigue in the sternocleidomastoid muscle dominant side in relation to the non-dominant side.